Kaempferol enhances intestinal repair and inhibits the hyperproliferation of aging intestinal stem cells in Drosophila - Zhao, Liusha; Luo, Ting; Zhang, Hong; Fan, Xinxin; Zhang, Qiaoqiao; Chen, Haiyang (Frontiers in Cell and Developmental Biology, 2024)
Introduction Intestinal stem cells (ISCs) are crucial for tissue repair and homeostasis because of their ability to self-renew and differentiate. However, their functionality declines significantly with age, resulting in reduced tissue regeneration and a higher risk of age-related diseases. Addressing this decline in ISC performance during aging presents a substantial challenge. The specific impact of nutrients or dietary elements on ISC adaptive resizing is urgent to explore. Methods Drosophila ISCs are an ideal model for studying development and aging because of their genetic richness, ease of manipulation, and similarity to mammalian tissues. As the primary mitotically active cells in the Drosophila gut, ISCs are flexible in response to dietary and stress signals. Manipulating signaling pathways or dietary restrictions has shown promise in regulating ISC functions and extending lifespan in flies, these approaches face broader applications for aging research. Results Kaempferol is well-regarded for its antioxidant, anti-inflammatory, and potential anticancer effects. However, its impacts on ISCs and the associated mechanisms remain inadequately understood. Our findings indicate that Kaempferol accelerates gut recovery after damage and improves the organism’s stress tolerance. Moreover, Kaempferol suppresses the hyperproliferation of aging ISCs in Drosophila. Further investigation revealed that the regulatory effects of Kaempferol on ISCs are mediated through the reduction of endoplasmic reticulum (ER) stress in aging flies and the modulation of excessive reactive oxygen species (ROS) levels via ER-stress pathways. Furthermore, Kaempferol exerts regulatory effects on the insulin signaling pathway, thereby contributing to the attenuation of ISC senescence. Discussion This study reveals that Kaempferol promotes intestinal homeostasis and longevity in aging flies by targeting ER stress and insulin signaling pathways, though the exact molecular mechanisms require further exploration. Future research will aim to dissect the downstream signaling events involved in these pathways to better understand how Kaempferol exerts its protective effects at the molecular level.